Economic considerations of biosafety and biotechnology regulations in India: Proceedings of a conference, August 24-25, 2006, New Delhi, India - International Food Policy Research Institute; Research and Information System for Developing Countries (International Food Policy Research Institute, 2007)
India was one of the first Asian countries to invest in agricultural biotechnology research and to set up a biosafety system to regulate the approval of genetically modified (GM) crops. Despite the Government of India’s acknowledged interest in encouraging growth in the biotechnology sector and the increasing number of research initiatives in the public and private domains, the approval of new applications of transgenic crops has been rather slow.